Μελέτη της ροής νετρονίων στο ΕΚΕΦΕ "Δημόκριτος" με τη χρήση των κωδίκων MCNP και NeuSDesc - Σιγαλός, Δημήτρης (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Εφαρμοσμένων Μαθηματικών και Φυσικών Επιστημών, 2015)
In the present work the quasi-monoenergetic neutron beam in the energy of 15.3 MeV, produced via the 3H(d,n)4He reaction at the 5.5 MV Tandem Van de Graaff accelerator at the NCSR "Demokritos", has been characterized. In absence of time-of-flight capabilities the characterization has been carried out through simulation with the combined use of the MCNP and NeuSDesc codes. In order to verify the simulated neutron energy spectra the multiple foil activation technique has been applied, implementing reactions with different threshold energies ranging from 0 to 10 MeV neutron energy. The verification was held through comparison of the simulated and experimental reaction rates of the selected reactions.